Optimal Design of C-Type Filter in Harmonics Polluted Distribution Systems - Tamaskani, Rohollah; Khodsuz, Masume; Yazdani-Asrami, Mohammad (Energies (Basel), 2022)
This paper aims to find the optimal size of parameters of a C-type filter in a non-sinusoidal system using a new optimization method called the Archimedes optimization algorithm (AOA). The inductance and capacitance values of the filter are acquired in which the power loss in the Thevenin resistor and the power loss characteristics of the load bus are minimized based on a new proposed objective function. Subject to technical and practical limitations of the IEEE 519 standard, an optimization problem is defined to achieve an optimal filter design that can increase the system power quality. The effectiveness of the proposed method is proved by comparison with the recent previously published methods. The results show the effectiveness of the proposed approach using the AOA in finding the minimum power losses and the harmonic content of frequency-dependent components. Eventually, the current study confirmed that the suggested objective function minimizes power losses of fundamental and harmonic order harmonics in non-sinusoidal systems.